A SURVEY OF ADVICE ON DRIVING IN NEUROLOGICAL CONDITIONS AMONGST NEUROLOGISTS AND NEUROSURGEONS. Issue 11 (9th October 2013) - Wong, Siew Lee; Sharrack, Basil
Abstract : Introduction: Doctors have the duty of care to provide driving advice to patients with certain neurological conditions. At the minimum, patients should be encouraged to inform the DVLA. This service evaluation aimed to survey the current practice of neurologists and neurosurgeons in the Sheffield Teaching Hospitals Foundation Trust with regards to giving appropriate driving advice to patients with certain neurological conditions as listed by the DVLA. Methodology: An anonymous questionnaire on whether driving advice was given was distributed to neurologists and neurosurgeons at consultant and specialist registrar levels over 3 days in January 2013. Conditions surveyed include epilepsy, brain tumour, peripheral neuropathy, Parkinson's disease, Multiple Sclerosis, narcolepsy, dementia, essential tremor, motor neurone disease and myasthenia gravis. All of those conditions were listed in the DVLA notifiable category1. Participants were required to select one of the four options: always, occasionally, never and not applicable, and to provide their own comments if wanted. Results: 41 questionnaires were sent out, and 33 responses were collected (response rate 80%). Driving advice on epilepsy was given 'always' in 82% and 'occasionally' in 18%. However, results were varied for other surveyed conditions–brain tumour (always: 48.5%, occasionally: 48.5%, never: 0%, not applicable: 3%), peripheral neuropathy (always: 3%, occasionally: 48.5%, never: 42.4%, not applicable: 6.1%), Parkinson's Disease (always: 42.4%, occasionally: 39.4%, never: 9.1%, not applicable: 9.1%), Multiple Sclerosis (always: 15.1%, occasionally: 60.6%, never: 18.2%, not applicable: 6.1%), narcolepsy (always: 54.4%, occasionally: 15.2%, never: 15.2%, not applicable: 15.2%), dementia (always: 48.5%, occasionally: 48.5%, never: 0%, not applicable: 3%), essential tremor (always: 0%, occasionally: 39.4%, never: 51.5%, not applicable: 9.1%), motor neurone disease (always: 12.1%, occasionally: 39.4%, never: 33.3%, not applicable: 15.2%), and myasthenia gravis (always: 12.1%, occasionally: 36.4%, never: 39.4%, not applicable: 12.1%). Discussion: This survey demonstrated that the neurologists and neurosurgeons were not consistent in giving driving advice to patients with notifiable neurological conditions. A significant proportion of the sampled population admitted to never giving advice to patients who may not be fit to drive. Possible reasons include the lack of knowledge and limited time available for discussion especially in the outpatient setting. This highlights the urgent need to educate and update clinicians on current DVLA requirements. Recommendations include inviting a DVLA representative to give a talk regarding current driving regulations in the neurosciences academic afternoon and including a tick box for 'Driving advice considered' in the Neurological clerking proforma to prompt clinicians.